Face Threats and Additional Reasons for Perceiving Support as Unwanted: A Study of Recently Diagnosed Cancer Patients. Issue 11 (2nd November 2017) - Ray, Colter D.; Veluscek, Alaina M.
ABSTRACT: This study investigated instances of support that were deemed unwanted by a recipient in the wake of a cancer diagnosis. The investigation was framed by politeness theory and considered the face threats evident in cancer patients' descriptions of unwanted support. Additional reasons for viewing support as unwanted, as well as the outcomes of receiving unwanted support, were also explored. Interviews ( N  = 15) were conducted with cancer patients who had been initially diagnosed within the previous 12 months. Analyses demonstrated that face threats are among the reasons for viewing some support as problematic; however, additional reasons beyond face threats also occurred. The most frequently occurring reasons for regarding support as unwanted were threats to the receiver's negative face and messages failing to convey empathy. Finally, the influence of receiving unwanted support on cancer patients is discussed in terms of recipients' ability to manage emotions, respond to the support, potentially view the support provider negatively, and assert greater control over future supportive interactions.